Artificial insemination: Key to improving livestock production efficiency - International Livestock Research Institute (International Livestock Research Institute, 2022)
Since 2020, the ‘Livestock-led interventions towards equitable livelihoods and improved environment in the Northwest Highlands of Vietnam’ or Li-chăn project has conducted training to improve livestock genetic capacity for farmers in the Chieng Chung and Chieng Luong communes. The training focused on (1) breeding techniques and artificial insemination (AI) for pigs and cows, (2) boar semen extraction and use of semen in AI, (3) AI of Ban pigs for farmers and vets, and (4) AI of cows by commune and village vets. The project has also helped communities arrange mass insemination of livestock enabling many households to have their Ban pigs inseminated at the same time, increasing output and attracting traders to purchase livestock in rural areas.